Investigation of the incidence of Toxoplasmosis and cytomegalovirus in patients with thalassemia - Ali Yonis Saleh; Adeba Y. Shareef Al-Numan (Tikrit Journal of Pure Science)
Blood transfusions was considered as a source of a number of infections in some cases if the donor is infected, especially the virus and parasitic ones, in which the blood is the main route of transport if it is contaminated from the environment or during the transport. The current study included testing (250) blood samples for Thalassemia patients and (100) blood samples from healthy subjects as a control , The samples included with (134) males and (116) females with mean age of (13.87 ± 9.37) years for patients and (14.08 ± 6.45) years for control samples. And for the period from February 2017 to July 2017 And patients who were diagnosed by specialists in Ibn al-Atheer teaching Hospital for Children in Nineveh Governorate. The study showed a high rate of infection with CMV infection in male thalassemia patients (42%) while in females (36.1%), the highest rate of infection was in the age group 16 years and above and the increase in the number of blood transfusions increases the rate of infection (46.5%) in patients received blood twice or more per month and decreased to (37.6%) in patients who receiving blood once a month. The highest rate of Toxoplasma infection was found in females (18.3%) while in males (15.6%). The highest age group (6-10) years showed the highest percentage of infection (19.1%). Blood infected patients with T. gondii recieving blood twice per month formed (21.9%) while  those receiving blood one time per month decreased to (15.9%) .